Comparative description of brown algae from the coastal zone of Far East - Natalia M. Aminina (Известия ТИНРО)
Data on stock and distribution of commercial and prospective for harvesting brown algae at the coast of Russian Far East are presented and compared. Their total biomass in the traditional harvesting grounds prevails 3.5 million tons. Saccharina japonica, Saccharina gurjanovae, Cystoseira crassipes have the highest biomass. However, taking into account both the stock and chemical composition of the tissues, Saccharina bongardiana, Arthrothamnus bifidus, and Eualaria fistulosa are the most profitable for harvesting and processing. The algae from the coastal waters of south-western Sakhalin have generally higher content of valuable proteins and minerals, but the content of mannitol and alginic acid is higher in the algae from the coastal waters of Kamchatka and Primorye. Contamination of the algae by toxic elements is considered, as well: in general, the safety indicators allow to regard all basic harvesting grounds of brown algae in the Far Eastern waters as suitable for commercial exploitation, though insignificant excess of the permissible level of lead (0.5 mg/kg) is detected for the brown algae from the coastal waters of Primorye and several sites in the Aniva Bay (southern Sakhalin).